Experimental validation of genetic selection for resistance against Streptococcus agalactiae via different routes of infection in the commercial Nile tilapia breeding programme. (20th October 2020) - Joshi, Rajesh; Skaaurd, Anders; Tola Alvarez, Alejandro
Abstract: The objective of this study was to validate the genetic selection for resistance to streptococcosis under experimental challenge conditions in a commercial population of Nile tilapia. Further, effects of using two different routes of infection of Streptococcus agalactiae ; intraperitoneal injection (IP) and cohabitation with the shedder fish (cohab), on the genomic parameters, prediction accuracy and response to selection are compared. The comparison was made between two different lines of fish; one selected for S. agalactiae resistance for one generation and randomly mated for two generations (to mimic the multiplication activities occurring in distribution channels and hatcheries); and the other unselected. 1, 500 fish, each from these two lines, were used for the experimental challenge test. Survival analysis using Kaplan–Meier estimators and Hazard's ratio was used to quantify differences in mortality between the two lines. Further genomic analysis was performed with 2, 684 fish and 35, 745 SNPs using both univariate and bivariate GBLUP models. Genetic selection for resistance to S. agalactiae led to the significant ( p  < .001) reduction in the risk of death by 65% in the selected line, compared to the unselected line. Similarly, the risk of death via cohabitation route of infection significantly ( p  < .01) decreased by 80%, compared to IP. The genetic correlation between these two routes of infection was ~0.9. Genetic selection changed the impact of the routes of infection, with the change in the distribution of estimated breeding values and the gain of 3.04 ± 1.25 days as selection response ( p  < .05).